Therapeutic Use of Music, Dance, and Rhythmic Auditory Cueing for Patients with Huntington’s Disease: A Systematic Review - Schwartz, Anna E. (J Huntingtons Dis, 2019)
BACKGROUND: Studies have assessed the therapeutic effect of music, dance, and rhythmic auditory cueing for patients with Huntington’s disease (HD). However, the synthesis of evidence in support of their positive impact on symptoms is lacking. OBJECTIVE: We conducted a systematic literature review to evaluate the potential benefits of music, dance, and rhythm on the cognitive, psychiatric and motor function in patients with HD. METHODS: Two- and three-keyword searches and a manual search identified medical literature published from 1999 through 2019. We considered literature that assessed outcomes of art-based rehabilitation programs or individual modalities for persons with early, middle, or advanced HD. Structured analysis was conducted using data entry tables with categories for patient health status, art methods, and outcomes. RESULTS: Seven articles and six abstracts met eligibility criteria, of which nine evaluated art-based rehabilitation programs. Studies mainly assessed cognitive, psychiatric, and motor functions through music, dance, or rhythm modalities. Although results were conflicting, in summary improvements to motor function were dependent on disease severity and more responsive to art therapy programs than rhythm-motor synchronization. Benefits to global cognition that resulted from rhythmic training correlated with microstructural changes. Qualitative data verified a positive impact on language production, chorea, behavior, and quality of life. CONCLUSIONS: Our review has shown a potential benefit of music, dance, and rhythm for patients with HD, which is particularly important for a disease that has no cure. Art forms seemed to affect cognitive, psychiatric, motor, psychosocial, and neuroanatomical domains. However, evidence is preliminary, warranting further investigation to establish the foundation for this field.